Therapeutic Effects of Static Magnetic Field on Wound Healing in Diabetic Rats - Jing Zhao; Yong-guo Li; Kai-qin Deng; Peng Yun; Ting Gong (Journal of Diabetes Research)
Objective. To investigate the effects of static magnetic field (SMF) on cutaneous wound healing of Streptozotocin- (STZ-) induced diabetic rats. Methods. 20 STZ-induced diabetic rats were randomly divided into two groups (10 in each group): diabetic rats with SMF exposure group which were exposed to SMF by gluing one magnetic disk of 230 mT intensity and diabetic rats with sham SMF exposure group (sham group). 10 normal Wistar rats were used as the control group. One open circular wound with 2 cm diameter in the dorsum was generated on both normal and diabetic rats and then covered with sterile gauzes. Wound healing was evaluated by wound area reduction rate, mean time to wound closure, and wound tensile strength. Results. The wound area reduction rate in diabetic rats in comparison with the control group was significantly decreased (P<0.01). Compared with sham magnet group, diabetic rats under 230 mT SMF exposure demonstrated significantly accelerated wound area reduction rate on postoperative days 7, 14, and 21 and decreased gross time to wound closure (P<0.05), as well as dramatically higher wound tissue strength (P<0.05) on 21st day. Conclusion. 230 mT SMF promoted the healing of skin wound in diabetic rats and may provide a non-invasive therapeutic tool for impaired wound healing of diabetic patients.